Effectiveness of obesity interventions in sub-Saharan Africa: A systematic review and meta-analyses. - Kingsley Agyemang; Shirley Crankson; Nana Anokye (PLoS ONE)
The escalating obesity epidemic in sub-Saharan Africa is a pressing regional concern. Despite this, there is scarce evidence of effective strategies to halt its upward trend in the region. We have, therefore, synthesised evidence on effective interventions to prevent and manage obesity in sub-Saharan Africa. We searched Scopus, PsycINFO, Cochrane Library, Web of Science and Medline for pertinent studies for this review. Studies were eligible if they focused on a sub-Saharan African country and assessed obesity/overweight with objective outcome measures. We examined their methodological quality with the Joanna Briggs Institute and the National Institutes of Health appraisal checklists. Publication bias was assessed with funnel plots. A meta-analysis with a random-effects model was fitted to explore the pooled effect of identified obesity interventions on anthropometric obesity measures. The heterogeneity of the studies was assessed using the I-square statistic. Our search yielded seven eligible studies for this review. Their quality ranged from moderate to high. The interventions identified included aerobic and resistance exercises, micronutrient supplementation and physical education. The meta-analysis revealed that aerobic and resistance training could significantly reduce obesity by approximately 34% (p = 0.04; 95%CI = -0.67 - -0.02). However, they do not significantly reduce waist circumference (Effect size = -1.14; 95%CI = -0.67-0.55; p = 0.19). Aerobic and resistance training exercises could be embedded in physical activity interventions to prevent and manage overweight and obesity in sub-Saharan Africa. PROSPERO registration number: CRD42023430503.